A strategy to address the challenge of electrochemical CO2 and N2 coupling to synthesis urea on two-dimensional metal borides (MBenes) by computational screening. (September 2022) - Xiao, Y.; Shen, C.; Xiong, Z.; Li, J.; Zhang, W.
Abstract: To achieve efficient urea formation via electrocatalytic C–N coupling, we proposed a new route for synthesizing urea on 2D metal borides (MBenes) by theoretical prediction. It has been reported that inert CO2 and N2 molecules can be converted into urea via electrocatalytic C–N bond coupling, which is a promising alternative method to industrial processes. However, due to the weak adsorption of and difficulty in activating CO2 and N2 molecules, the reaction of C–N coupling is challenging to achieve. To ensure C–N bond coupling between *NN* and *CO to form *NCON intermediates, which act as the key precursor to urea formation, the utilization of sustainable energy (solar energy) can be helpful in addressing the challenge of electrochemically synthesizing urea. Furthermore, computational screening provides an effective way to gain insight into the mechanisms of the C–N coupling and protonation steps. It is also beneficial for guiding the development of the sustainable synthesis of carbon nitride chemicals via C–N coupling, and we believe it will attract full attention in the future. A new theoretical strategy was used to screen efficient catalysts for urea electrosynthesis based on coupling CO2 and N2 to generate H2 NCONH2 . We established the Gibbs free energy landscape and calculated the limiting potential based on the rate-determining step, and a volcano plot was constructed as a function of ΔG(*NCON) to predict MBenes for urea formation. It included the kinetic stability, CO2 and N2 adsorbability, catalytic activity, and urea synthesis selectivity. It is demonstrated that Mo2 B2 and Ru2 B4 are suitable urea electrosynthesis catalysts with high activity and selectivity. This work can contribute to the application of C–N coupling electrochemical reactions. Graphical abstract: Image 1 Highlights: MBene compounds can serve as promising catalyst for urea synthesis. MBene ensured excellent thermodynamic stability for C–N coupling formation. MBenes have high-performance catalysts to capture and reduce urea. Volcano curve dependence as function of NCON binding strength descriptors.